Powerful Intellectual Resources of the Russian Foreign Policy (A Reliable Resource of the Foreign Policy Review) - V. I. Mizin (Vestnik MGIMO-Universiteta)
The article describes the activities of the Institute of International Studies of MGIMO-University which are devoted to the research and academic support of the foreign policy of the Russian Federation.